Determinants of success and failure in the internationalisation of the cork business: A tale of two Iberian family firms - Jo\~ao Lopes; Amélia Branco; Francisco Parejo; Jose Rangel (European Regional Science Association (ERSA), 2014)
The trajectories of internationalisation followed by family firms can be viewed from several theoretical approaches ? phases of the internationalisation process; international entrepreneurship, sociological perspective, family business theory. An historical perspective of the internationalised family firms, allowing the integration of these several approaches, is useful to a deep understanding of the internationalisation process of different sectors and countries. The main purpose of this paper is to identify the facilitating and the restricting factors during the internationalisation path of family firms, considering their competitive advantages, the ownership structure and management attitudes, innovation and intangible assets and other relevant factors, internal and/or external to the firm. It makes a long run analysis (more than one century) of two companies acting in the cork business in Spain and Portugal: Mundet and Amorim&Irm\~aos. One of these companies - Mundet ? has been closed in the 1980s and the other - Amorim&Irm\~aos ? became, and is by now, the leading company in the cork worldwide business. The careful comparison of these two stories, one of failure and the other of success, allows an accurate identification of the determinants of a successful internationalisation. In fact, it is useful for understanding several characteristics of both firms, some similar and other different, allowing the test of several hypothesis in the context of the theoretical approach to the internationalisation of family firms. First of all, both are family firms operating in the same business and since their origin orientated to foreign markets. Second, their story went along much of the twentieth century and so both faced similar national and international constraints but in the end both became leading firms in the cork business, although in different time periods. Third, their location choices were different and, although in both cases benefiting from agglomeration forces in certain phases of the business, they were also important determinants of the opposite destinies of these two emblematic Iberian cork family firms.
Keywords: F23; L73; N60; O14; R12; 330